A Systematic Review of Laparoscopic Cholecystectomy in Situs Inversus - Mohamed Ali Chaouch; Hichem Jerraya; Mohamed Wejih Dougaz; Ramzi Nouira; Chadli Dziri (Journal of Investigative Surgery, 2021)
Background: In case of situs inversus (SI), laparoscopic cholecystectomy (LC) is challenging. This systematic review aimed to assess the appropriate technique for LC in SI. Methods: An electronic search was carried out using the following keywords: “Situs inversus” and “Laparoscopic cholecystectomy”. The main endpoints were surgical procedures, intra-operative cholangiography (IOC) use, common bile detection, operative time, bile duct injury, conversion, mortality, and morbidity. Results: We retained 93 cases. Essentially two types of laparoscopy port placement reported were reported: the “American mirror technique” and the “French mirror technique”. One report of a left-handed surgeon was retained. Fourteen cases operated by a right-handed surgeon: “American mirror technique” used in 33 cases and “French mirror technique” used in 7 cases. The operative time was mentioned in 52 cases with a mean of 74 min without any statistical difference between the two techniques. No cases of postoperative death, major complications or bile duct injury were reported. IOC was performed in 16 cases (17.2%). An associated common bile duct stone was found in eight cases (8.6%). ERCP with endoscopic sphincterotomy was used to treat the associated CBD stones in 7 cases and a choledecoscopy was conducted in one case to extract stones. The conversion rate in this systematic review was 1.07%. Conclusions: LC in SI is easier for left-handed surgeons. The fastest technique for right-handed surgeons seems to be the “American mirror technique” and some modifications of the port placement can facilitate it.